Sweet tooth. The complete first season [videorecording (DVD)] - Convery, Christian, 2009-; Anozie, Nonso, 1979-; Akhtar, Adeel; Lemire, Jeff (Warner Home Video, 2022)
A decade after "The Great Crumble" wreaked havoc on the world and led to the mysterious emergence of hybrids (babies born part human, part animal), a sheltered hybrid deer-boy named Gus unexpectedly befriends a wandering loner named Jepperd. Together they set out in search of answers about Gus's origins, Jepperd's past, and the true meaning of home.